2003
DOI: 10.1111/1475-6773.00113
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in the Purchase of Nongroup Health Insurance: The Roles of Community and Family‐Level Factors

Abstract: Objective. To evaluate the influence of community-and family-level factors on racial/ ethnic disparities in the uptake of nongroup (individual) health insurance. Data Sources. Responses to the 1996-1997 Community Tracking Study Household Survey plus community-level descriptors from several sources including census data, the Area Resource File, and community and migrant health center Medicare cost reports. Study Design. Logistic regression was used to compare families in which at least one person had nongroup h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Quality of services was the most important consideration that potential buyers would have to purchase BHI among respondents in all willingness to pay models compared to cost, distance or need factors. As highlighted by several studies, Mexican immigrants, both documented and undocumented, continue to face significant quality of care barriers in the US and are less likely to purchase individual health insurance [20]. BHI could potentially meet Mexican migrants' need for quality care through culturally competent providers and services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quality of services was the most important consideration that potential buyers would have to purchase BHI among respondents in all willingness to pay models compared to cost, distance or need factors. As highlighted by several studies, Mexican immigrants, both documented and undocumented, continue to face significant quality of care barriers in the US and are less likely to purchase individual health insurance [20]. BHI could potentially meet Mexican migrants' need for quality care through culturally competent providers and services.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified both demographic factors and health insurance plan characteristics that motivate consumers to purchase private non-group health insurance [20][21][22]. Attitudes towards health coverage and perceived need are important influences where individuals who consider themselves healthy are often less likely to perceive the need for insurance coverage [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Such a comprehensive effort has the potential to identify the system-related sources of racial/ethnic disparities in cancer screening and ultimately, to hasten the reduction of the cancer burden among disadvantaged racial groups, particularly those we know little about. Policy makers may miss unmet needs of vulnerable groups that are masked by general population studies on HMO organizational structure.…”
Section: Ponce Et Almentioning
confidence: 99%
“…[14][15][16][17] As a result, descriptive differences in out-of-pocket spending may understate the causal effect of employmentrelated insurance relative to individual insurance because people who currently have individual insurance are likely to need less care than those with employment-related insurance.…”
mentioning
confidence: 99%